Single-cell transcriptomics identifies the common perturbations of monocyte/macrophage lineage cells in inflammaging of bone marrow - Peng Liao; Sihan Tong; Lin Du; Jiong Mei; Bingqi Wang; Yafei Lu; Meng Yao; Changqing Zhang; Delin Liu; Zhigang Zhong; Fang Ye; Junjie Gao (Journal of Orthopaedic Translation, 2025)
Background: Bone marrow inflammaging is a low-grade chronic inflammation that induces bone marrow aging. Multiple age-related and inflammatory diseases involve bone marrow inflammaging. Whether common pathological pathways exist in bone marrow inflammaging remains unclear. Methods: We collected bone marrow from telomerase-deficient mice (telomerase RNA component, TERCko/ko), 5 × FAD mice and Dmp1Cre-DTAki/wt mice and High-fat diet-fed mice (HFD), and lumbar 5 nerve compression mice. We performed scRNA-Seq analysis on bone marrow obtained from these mouse models to investigate the potential shared pathway of bone marrow inflammation. Results: We identified the monocyte/macrophage lineage was activated via the App-Cd74 axis in multiple aging and inflammatory mouse models. Increased expression of CD38 and Ly6a, and decreased expression of Col1a and Lif in macrophages serve as shared changes in different mouse models. The activated macrophages, interacting with other cells, control the expansion of B cells via the CD52-Siglec-G axis. The Ccl6-Ccr2 and Ccl9-Ccr1 ligand-receptor pairs, along with Fn1 and C3-related pathways in macrophages, were associated with immune cell activation and the recruitment of lymphocytes. Interactions with mesenchymal cells were enriched for integrins (Itga4), Fn1, and adhesion molecules (Vcam1). Conclusion: Our study demonstrates that monocyte/macrophage lineage stimulation is a key event in bone marrow inflammaging. We identified common differentially expressed genes and activated pathways in this lineage, suggesting potential targets for future interventions. The translational potential of this article: Our study revealed shared genes and ligand-receptor pairs in the activated monocyte/macrophage lineage within inflammaging bone marrow. These findings offer potential therapeutic targets for cell-specific anti-inflammatory treatments.